Analysis of Shop Sign Colors in Joong-Gu, Seoul — Nadulgage and Convenience Stores - SeongJin Kim (Journal of Asian Architecture and Building Engineering, 2017)
The South Korean government is attempting to revive small supermarkets by branding them as ″Nadulgage.″ These efforts include support to change retail store signs; however, in reality, the government has only provided emblem designs thus far. Based on previous studies, this study reviews the current status and features of sign colors for both Nadulgage and convenience stores in the Jung-gu area. In addition, after analyzing color images using the Moon–Spencer Theory, PCCS tone chart and I.R.I Color Emotional Quotient as analysis tools, we compare the characteristics of Nadulgage and convenience stores and draw our implications. The colors of Nadulgage signs still display the characteristics of colors that were elucidated in previous research. Moreover, the dominant colors of Nadulgage signs have a higher ratio of colors belonging to the contrast area compared with those belonging to the other groups. This makes their impression confusing when compared with the impression of the colors of convenience store signs. Therefore, reselection of the dominant colors that can portray the unique identity of a Nadulgage should be prioritized, and the color-matching relationship between dominant colors, assorted colors, and accent colors should be established in more detail. Thus, comparing Nadulgage and convenience stores may help in obtaining useful data.